IMPLEMENTASI STRATEGI BISNIS SM ENTERTAINMENT DI PASAR TIONGKOK MELALUI WAYV PADA TAHUN 2019-2021 - Prasasti Ramadhina Putri Pradana; Adiasri Putri Purbantina (Jurnal Bisnis Terapan, 2022)
SM Entertainment is the largest multinational company in the entertainment industry in South Korea, which founded in 1995 by Lee Soo Man. SM Entertainment as the first entertainment company to export K-POP music abroad, one of which is the Chinese market. SM Entertainment started to enter the Chinese market in the early 2000s by holding concerts as one of the promotions of their music. SM Entertainment is still developing and distributing the Hallyu products despite the difficulties for foreign companies to enter the Chinese market. SM Entertainment maintains their business in China with a strategy that has been adapted to the market environment there. This paper discusses SM Entertainment's marketing mix strategy through the boy group named WayV in order to maintain its business in China after the conflict of Terminal High Altitude Area Defense (THAAD). Using a qualitative research approach, this study aims to analyze SM Entertainment's marketing mix strategy implemented through WayV in 2019-2021 through three stages; segmenting, positioning, and targeting. This study explores how SM Entertainment's marketing mix strategy as the MNC's can maintain their market in China through WayV.